A "turn-on" near-infrared fluorescent probe with high sensitivity for detecting reduced glutathione based on red shift in vitro and in vivo. (January 2020) - Wang, Kaiping; Nie, Gang; Ran, Siqi; Wang, Huiling; Liu, Xiqiu; Zheng, Ziming; Zhang, Yu
Abstract: Fluorescence imaging has become a powerful tool for detecting reduced glutathione (GSH) to comprehend the physiological and pathological roles of GSH and the potential clinical diagnosis of GSH-related diseases, such as AIDS, liver damage, cancer, and leucocyte loss. High sensitivity and high selectivity remain challenges for near-infrared fluorescent probes to monitor GSH. Herein, a "turn-on" near-infrared fluorescent probe (HCG) was designed and developed in a convenient synthetic procedure, which had high sensitivity and selectivity to detect GSH based on the red shift of Schiff base. HCG could discriminate against amino acid that resemble GSH to monitor GSH in vitro . The fluorescence emission intensity linearly increased with an increasing concentration of GSH in the range of 0–16 μM, with a detection limit of 252 nM. HCG exhibited a diminutive detection limit (0.5 μM in actual experiments), a fast response time (30 s) and low cytotoxicity. The detection mechanism was confirmed by HPLC and HRMS spectra. Furthermore, HCG exhibited an excellent capacity for fluorescence imaging and has been successfully applied to detect endogenous GSH in three living cells. Finally, the bio-distribution of GSH in BALB/c mice was studied by using HCG. The results suggest that HCG has potential utility in biological science research. Graphical abstract: In this manuscript, a "turn-on" near-infrared fluorescent probe was developed and applied to monitor glutathione (GSH) with excellent sensitivity and selectivity in vitro . The novel probe HCG was successfully applied to detect endogenous and exogenous GSH in three living cells and the bio-distribution of GSH in BALB/c mice.Image 1 Highlights: A "turn-on" near-infrared fluorescent probe was developed for monitoring GSH with facile synthetic procedures. Based on Schiff base redshift, the probe exhibited high selectivity and high sensitivity to detect GSH in vitro. The probe served as bioimging tool for detecting endogenous and exogenous GSH in three living cells. The bio-distribution of GSH in BALB/c mice was studied through fluorescent imaging of HCG.